Bhutan’s Business Infrastructure Policy and Industrial Parks - World Bank (World Bank, Washington, DC, 2019)
Between 2010 and 2018, Bhutan’s economic performance in the real growth of gross domestic product (GDP) was respectable, averaging more than 5 percent a year. This was driven by hydropower, services, and agriculture. However, there is growing pressure to diversify production. Hydropower development will peak by 2023 and is associated with widening current account deficits and the accumulation of public debt. There is a greater need to foster a dynamic private sector and create employment. In this context, Bhutan has recently embarked on a strategy to develop a business infrastructure policy. This is mainly focused on establishing four industrial parks to jump-start investment and developing the management arrangements. These industrial parks would include access to land, infrastructure, and energy sources and be in the south, near the border with India. Drawing on the experiences of other countries, the industrial park policy in Bhutan is based on an overall umbrella of rules on purpose, coverage, policy considerations, existing infrastructure, regulatory and legal framework, and enactment and implementation of legislation. The industries in the parks are envisaged to include wood-based, agriculture-based, and metal-based industries.